Da'wah Strategy in the Contemporary Era of Hadith Perspective - Rosyad, Sabilar; Millah, Mus’idul (Universitas Ahmad Dahlan, 2023)
Da'wah strategy is an effort carried out to spread religious teachings with the aim of influencing the understanding, attitudes and behavior of individuals in society. This article discusses several da'wah strategies that are effective in achieving this goal. First, the personal approach strategy involves direct interaction with individuals through communication that is empathetic, persuasive, and respects differences. Second, the strategy of utilizing mass media and information technology utilizes print media, television, radio, and the internet to spread da'wah messages en masse. Third, the education and training strategy involves forming da'wah cadres who have good religious knowledge and effective communication skills. Fourth, the social engagement strategy encourages preachers to engage in social activities that benefit the community, such as economic empowerment, health services or disaster management. Fifth, the contextual approach strategy involves adjusting the da'wah message to the culture, social context, and challenges faced by the target community. In implementing these strategies, preachers can have a positive impact in shaping a better understanding and religious life in society.